2007
DOI: 10.1158/1078-0432.ccr-06-1192
|View full text |Cite
|
Sign up to set email alerts
|

The Suppression of Aurora-A/STK15/BTAK Expression Enhances Chemosensitivity to Docetaxel in Human Esophageal Squamous Cell Carcinoma

Abstract: Purpose: We previously reported that the expression of Aurora-A was frequently up-regulated in human esophageal squamous cell carcinoma (ESCC) tissues as well as cell lines and the upregulation contributed to a poor prognosis. In this study, we assessed the possibility of Aurora-A suppression as a therapeutic target for ESCC using ESCC cell lines. Experimental Design: We established subclones using vector-based short hairpin RNA (shRNA). Then, we investigated the effect of Aurora-A suppression on proliferation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 30 publications
3
37
1
Order By: Relevance
“…That has lead to test the proposal, in several laboratories, that experimental manipulation of the expression of genes coding for these proteins may be combined with MT-targeting drugs to improve their therapeutical efficacy. Well-documented instances include the genes encoding the mitotic protein kinases PLK1 (Spa¨nkuch et al, , 2007 and Aurora-A (Anand et al, 2003;Jiang et al, 2003;Hata et al, 2005;Tanaka et al, 2007), the MT-binding protein stathmin/ OP18, which has MT-destabilizing activity (Iancu et al, 2000(Iancu et al, , 2001Alli et al, 2002), and survivin, a member of the kinetochore-associated passenger proteins with MTstabilizing activity (Giodini et al, 2002;Carvalho et al, 2003;reviewed by Altieri, 2008). Relevant to the work reported here, survivin has been recently found to interact directly with Ran (Xia et al, 2008a, b).…”
Section: Discussionmentioning
confidence: 99%
“…That has lead to test the proposal, in several laboratories, that experimental manipulation of the expression of genes coding for these proteins may be combined with MT-targeting drugs to improve their therapeutical efficacy. Well-documented instances include the genes encoding the mitotic protein kinases PLK1 (Spa¨nkuch et al, , 2007 and Aurora-A (Anand et al, 2003;Jiang et al, 2003;Hata et al, 2005;Tanaka et al, 2007), the MT-binding protein stathmin/ OP18, which has MT-destabilizing activity (Iancu et al, 2000(Iancu et al, , 2001Alli et al, 2002), and survivin, a member of the kinetochore-associated passenger proteins with MTstabilizing activity (Giodini et al, 2002;Carvalho et al, 2003;reviewed by Altieri, 2008). Relevant to the work reported here, survivin has been recently found to interact directly with Ran (Xia et al, 2008a, b).…”
Section: Discussionmentioning
confidence: 99%
“…HEEpiC cells were purchased from ScienCell Research Laboratories (Carlsbad, CA) and were cultured according to the manufacturer's instructions (14). The human ESCC cell lines KYSE-150, -170, -190, and -590 were maintained as described previously (14,15). KYSE-170 cells were transfected with oligoribonucleotides for miR-210 or negative control RNA (ncRNA) (Ambion, Austin, TX) using HiPerFect transfection reagent (Qiagen, Valencia, CA) according to the manufacturer's protocol for overexpression.…”
Section: Methodsmentioning
confidence: 99%
“…Assay of Cell Proliferation, Cell Cycle, and Cell Death-The WST-1 assay to measure cell proliferation and flow cytometric assays to analyze the cell cycle and cell death were performed with KYSE-170 cells at 48 h after transfection as described previously (15). Calculations for the analysis of the cell cycle were performed with ModFit software (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…(32) For esophageal squamous cell carcinoma cells, inhibition of Aurora-A suppressed tumor growth and sensitized the cells to docetaxel chemotherapy. (29) Moreover, our previous study showed that suppression of Aurora-A by VX-680 led to 46.0% tumor growth suppression, (33) suggesting Aurora-A might be a promising therapeutic molecular target for NPC and other types of HNSCC. However, the prognostic effect of Aurora-A has not been characterized in human NPC.…”
mentioning
confidence: 98%
“…(25) Indeed, Aurora-A overexpression has been found in a variety of malignancies, not only in solid tumors but also in leukemia, and predicted an inferior patient outcome. (25)(26)(27)(28)(29) Upregulation of Aurora-A mRNA, for example, was correlated with the occurrence of regional lymph node metastasis for HNSCC. (30,31) Conversely, inhibition of Aurora-A by its specific small molecule inhibitor VX-680 potently suppressed the laryngeal HepG2 cell AKT1/2 phosphorylation as well as migration capacity, and sensitized the cell to X-ray irradiation.…”
mentioning
confidence: 99%